1991
DOI: 10.1111/j.1574-6968.1991.tb04738.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of the serine protease active site in the mode of action of epidermolytic toxin ofStaphylococcus aureus

Abstract: The sequences of the epidermolytic toxins and V8 serine proteinase share about 25% identity, including the catalytic triad at the proteinase active centre. Here we have altered the putative ETA active‐site serine‐195 to glycine by site‐directed mutagenesis. No epidermolytic activity was detected when up to 100‐fold greater amounts of the homogeneous mutant ETA were injected subcutaneously into neonatal mice showing that serine‐195 is required for toxicogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…Immunocytochemical studies have shown that the toxin binds to the filaggrin group of proteins in keratohyalin granules,14and because filaggrins act as intracellular anchors of desmosomes, many investigators have speculated that epidermal splitting is a result of rupture of these desmosomes, probably from proteolytic activity of the toxins 15-17. The toxins in their native form, however, do not have any significant proteolytic activity,18 19 and the hypothesis that they may be serine proteases comes from indirect evidence: (1) both toxins show significant sequence homology with the staphylococcal V8 protease, particularly in the region of the serine–aspartic acid–histidine catalytic triad that forms the active site of trypsin-like serine proteases15 ; (2) replacing any of the three amino acids that form the catalytic triad of the toxins results in complete loss of biological activity when injected into newborn mice16 17 19; (3) incubation of ETA with neonatal mouse epidermis18 or neonatal mouse epidermal extract19 results in the induction of caseinolytic activity in the supernatant; and (4) recent computer modelling 20 and crystallographic studies21 22on the three dimensional structure of the toxins have revealed a high degree of structural similarity with known glutamate specific trypsin-like serine proteases. Deletion studies have shown that the highly charged amino terminal of the exfoliative toxins is essential for their activity,22 and recent structural studies have led to speculation that this region may be responsible for binding an epidermal receptor, which in turn may result in a conformational change that exposes the toxin’s active catalytic site 21…”
Section: The Toxinsmentioning
confidence: 99%
“…Immunocytochemical studies have shown that the toxin binds to the filaggrin group of proteins in keratohyalin granules,14and because filaggrins act as intracellular anchors of desmosomes, many investigators have speculated that epidermal splitting is a result of rupture of these desmosomes, probably from proteolytic activity of the toxins 15-17. The toxins in their native form, however, do not have any significant proteolytic activity,18 19 and the hypothesis that they may be serine proteases comes from indirect evidence: (1) both toxins show significant sequence homology with the staphylococcal V8 protease, particularly in the region of the serine–aspartic acid–histidine catalytic triad that forms the active site of trypsin-like serine proteases15 ; (2) replacing any of the three amino acids that form the catalytic triad of the toxins results in complete loss of biological activity when injected into newborn mice16 17 19; (3) incubation of ETA with neonatal mouse epidermis18 or neonatal mouse epidermal extract19 results in the induction of caseinolytic activity in the supernatant; and (4) recent computer modelling 20 and crystallographic studies21 22on the three dimensional structure of the toxins have revealed a high degree of structural similarity with known glutamate specific trypsin-like serine proteases. Deletion studies have shown that the highly charged amino terminal of the exfoliative toxins is essential for their activity,22 and recent structural studies have led to speculation that this region may be responsible for binding an epidermal receptor, which in turn may result in a conformational change that exposes the toxin’s active catalytic site 21…”
Section: The Toxinsmentioning
confidence: 99%
“…Primary sequence numbers of the ETs refer to the linear sequence of the mature protein followed by topological equivalences of R-chymotrypsinogen in parentheses(6,22) 3. Substrate residues are represented by Pn, ..., P2, P1, P1′, P2′, ..., Pn′, where the bond is cleaved between P1-P1′, while Sn, ..., S2, S1, S1′, S2′, ..., Sn′ represents the corresponding binding sites on the protein following the convention of Schechter and Berger(27) 4.…”
mentioning
confidence: 99%
“…Both toxins cause intraepidermal cleavage through the granular layer, without epidermal necrolysis or an inflammatory response of the skin (6,19,27). Several lines of evidence have suggested that ETs act as serine proteases to induce intraepidermal cleavage: (i) amino acid sequences of ETA and ETB show similarity with the S. aureus V8 serine protease (17), and the catalytic site of V8 protease is conserved in ETA (7); (ii) partially purified ETs preincubated with serine protease inhibitors exhibit delayed skin exfoliation (17); (iii) replacement of the serine residue with glycine in the putative catalytic site of ETA completely abolishes the exfoliative activity of the toxin (35,38); and (iv) crystal structures of ETA (13,53) and ETB (52) have recently been determined, and both types were shown to structurally belong to the chymotrypsin family of serine proteases. However, the exact target substrate was a mystery for 30 years, until the pathogenic role of ET was demonstrated in 1970 by using neonatal mice (29).…”
mentioning
confidence: 99%